Locomotor Muscles in COPD: The Rationale for Rehabilitative Exercise Training - Marillier, Mathieu; Bernard, Anne-Catherine; Vergès, Samuel; Neder, J. Alberto (Frontiers in Physiology, 2020)
Exercise training as part of pulmonary rehabilitation is arguably the most effective intervention to improve tolerance to physical exertion in patients with chronic obstructive pulmonary disease (COPD). Owing to the fact that exercise training has modest effects on exertional ventilation, operating lung volumes and respiratory muscle performance, improving locomotor muscle structure and function are key targets for pulmonary rehabilitation in COPD. In the current concise review, we initially discuss whether patients’ muscles are exposed to deleterious factors. After presenting corroboratory evidence on this regard (e.g., oxidative stress, inflammation, hypoxemia, inactivity and medications), we outline their effects on muscle macro- and micro-structure and related functional properties. We then finalize by addressing the potential beneficial consequences of different training strategies on these muscle-centered outcomes. This review provides, therefore, an up-to-date outline of the rationale for rehabilitative exercise training approaches focusing on the locomotor muscles in this patient population.